Islamic Education Marketing Strategy in Admission of New Students - Kacung Wahyudi; Mad Sa'i (Maharot : Journal of Islamic Education, 2023)
Competition in the world of education is very tight, this is due to the many existing educational institutions. The problem that is often faced by educational institutions is the decrease in new students every year. This is due to the lack of effective marketing strategies carried out by educational institutions. The aims of the research are marketing strategy, implementation of marketing strategy, supporting and inhibiting factors, as well as solutions to overcome obstacles to the implementation of Islamic education marketing in the acceptance of new students at MTs Matsaratul Huda Panempan Pamekasan. This research uses a qualitative descriptive method. Sources of data obtained through observation, interviews, and documentation. While the data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this study indicate that: first, namely forming a new student acceptance team, marketing mapping, determining media or marketing tools. Secondly, distributing brochures or promotions and carrying out the stages of accepting new students so as to increase the number of students in 2022/2023. Third, the supporting factors are having superior programs, human resources, and media. Meanwhile, the inhibiting factor is intense competition, students don't want to choose between MTs and SMP, constrained by the network. Fourth, for competition, namely improving the quality of institutions and evaluating marketing strategies, for discrepancies by holding deliberations and submitting to foundations, and network constraints by providing modems when implementing new student admissions.